Nirmasi (Delphinium) poisoning with salvoes of malignant ventricular arrhythmias in central Nepal: A case report - Laudari, Shankar; Murtuza, Shahid; Bhusal, Santosh Sharma; Yadav, Rachit (Journal of National Heart and Lung Society Nepal, 2023)
Nirmasi is a commonly used herb in Nepal especially in hilly and Himalayan regions. It is known as Delphinium species herb. Nirmasi has been used in Nepalese and Indian rural communities since ages for treatment of chronic illnesses like headache, epilepsy, mania, paralysis, rheumatism, toothache, and various types of pain. However, many species of Nirmasi (Delphinium) are poisonous and look quite similar in morphology to the beneficial ones. As a result, unintentional poisoning is common. Poisoning due to these plant products results in various symptoms attributed to gastric irritation, competitive neuromuscular blockade, and cardiotoxicity caused by various alkaloids present in them. We report here a case of poisoning due to Nirmasi herb ingestion presenting as epigastric pain, vomiting, profuse sweating, syncopal attack, hypotension and malignant ventricular arrhythmias managed successfully with antiarrhythmics and supportive treatment.